Micropulse Laser in Glaucoma - Alka Pandey (Delhi Journal of Ophthalmology)
A new type of diode laser-Cyclo G6 or the micropulse laser is helpful in reducing the intraocular pressure in glaucoma. It is a 810 diode laser from Iridex Corporation similar to the trans-scleral cyclophotocoagulation (TSCPC) laser but with a difference. The laser is delivered in a continuous wave fashion in TSCPC whereas in micropulse, it is delivered in short bursts with an “on time”and an “off time”. This “off time” helps the target tissue to cool down in between, thereby greatly reducing thermal damage. Thus, this could prove to be an excellent non-surgical option for glaucoma patients.